Survival of patients treated with extracorporeal hemoadsorption and extracorporeal membrane oxygenation: results from a nation-wide registry - Heidenreich, Adrian; Kaier, Klaus; Bode, Christoph; Zehender, Manfred; von zur Mühlen, Constantin; Dürschmied, Daniel; Wengenmayer, Tobias; Stachon, Peter; Supady, Alexander (ASAIO journal, 2023)
Extracorporeal hemoadsorption with the CytoSorb adsorber is increasingly being used during the past years. The use in combination with extracorporeal membrane oxygenation (ECMO) is feasible, but frequency of its use and outcomes have not been assessed in larger cohorts. We analyzed all patients treated with veno-venous (VV) ECMO either with or without CytoSorb in Germany from 2017 to 2019. Data were retrieved from a nationwide claim dataset collected by the Research Data Center of the Federal Bureau of Statistics. During this three-year episode, 7,699 patients were treated with VV ECMO. Among these, the number of CytoSorb-treated patients constantly increased from 156 (6.6%) in 2017 to 299 (11.8%) in 2019. In this large cohort hemoadsorption with the CytoSorb adsorber was associated with higher mortality and increased treatment costs. Due to limited information in the dataset about the severity of disease comparison of outcomes of patients treated with and without CytoSorb has to be interpreted with caution. Further studies have to examine if this finding is due to a negative effect of hemoadsorption with the CytoSorb device or is rather to be attributed to disease severity.